Application of 2D numerical simulation for the analysis of the February 2014 Bolivian Amazonia flood: Application of the new HEC-RAS version 5. Issue 1 (1st January 2016) - Quirogaa, V. Moya; Kurea, S.; Udoa, K.; Manoa, A.
Abstract: Llanos de Moxos are vast plains in the Bolivian Amazonia that are continually flooded by the Mamoreriver. The flood lasts for several days affecting important cities like Trinidad, drowning people, drowning cattle and swamping arable land. Because of the cloudy skies, remote sensing observations are limited to some areas and few days. Thus, there is huge uncertainty about characteristics of flood events and possible consequences. Two-dimensional (2D) numerical simulation proved to be an important tool for understanding flood events. The HEC-RAS model is one of the most popular hydraulic models. In 2014 a new version of HEC-RAS (HEC-RAS-v5) was released including 2D capabilities. The present study applied the new HEC-RAS-v5 to simulate the February 2014 flood event in the Bolivian Amazonia. The flood simulated shows good performance when compared with satellite image of the flood event. In addition, the simulation provides information like water depth, flow velocity and a temporal variation of the flood. Specific locations where water begins to overflow were identified. Over most of the flooded area the water velocity is lower than 0.25 m s −1 . During first ten days of the flood the flood extent increases rapidly. The flood depth allows identifying areas exposed to different hazard levels. The west plain of the Mamore river is the most exposed to the flood; it shows bigger flood extent, longer flood duration and deeper water depth. The flood that threatens the city of Trinidad originates in two locations; one located 32 km at the north and other located 10 km at the south west. The flood from the north gets close to Trinidad twelve days after it begins to overflow, while the flood from the south gets close to Trinidad seven days after it begins to overflow. Although the flood from the north is deeper than the flood from the south, the flood from the south begins flooded before the north. Thus, water borne and vector borne diseases may originate at the south earlier than the north. The city of San Javier gets covered by flood five days after the water begins to overflow. The study shows the applicability and the value of the 2D capabilities of the new HEC-RAS for flood studies.